2021
DOI: 10.3390/cancers13235944
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA (lncRNA) in Oral Squamous Cell Carcinoma: Biological Function and Clinical Application

Abstract: Oral squamous cell carcinoma (OSCC) is a type of malignancy with high mortality, leading to poor prognosis worldwide. However, the molecular mechanisms underlying OSCC carcinogenesis have not been fully understood. Recently, the discovery and characterization of long non-coding RNAs (lncRNAs) have revealed their regulatory importance in OSCC. Abnormal expression of lncRNAs has been broadly implicated in the initiation and progress of tumors. In this review, we summarize the functions and molecular mechanisms r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 151 publications
0
16
0
Order By: Relevance
“…LncRNAs are characterized by their large number, variety and mode of action. At present, there is no uniform classification standard for lncRNAs [ [18] , [19] , [20] ]. According to the localization of lncRNAs in cells, they can be divided into cytoplasmic lncRNAs and cytosolic lncRNAs, some of which are located in both the nucleus and the cytoplasm [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are characterized by their large number, variety and mode of action. At present, there is no uniform classification standard for lncRNAs [ [18] , [19] , [20] ]. According to the localization of lncRNAs in cells, they can be divided into cytoplasmic lncRNAs and cytosolic lncRNAs, some of which are located in both the nucleus and the cytoplasm [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral lichen planus (OLP) is a premalignant epithelial oral lesion, with the potential to malignantly transform [ 33 ]. Oral squamous cell carcinoma (OSCC) is a malignant epithelial tumor with low overall survival rates and poor prognosis, regardless of the advances in surgery, chemotherapy, and radiotherapy [ 34 ]. Growing evidence supports an association between oral squamous cell carcinoma (OSCC) and chronic inflammation and the involvement of long non-coding transcriptome alterations [ 34 ].…”
Section: Ncrnas and Oral Inflammatory Diseasesmentioning
confidence: 99%
“…Similar to lncRNAs, circRNAs can directly bind to downstream proteins and affect their functions. Numerous reviews have summarized the potential contribution of these non-coding RNAs in the malignant progression of HNSCC via regulation of cell proliferation, metastasis potential, glucose metabolism, drug resistance, cancer stemness, and so on [ 47 , 48 , 49 ]. Likewise, accumulating data indicated that non-coding RNAs may also play a significant role in the regulation of ferroptosis in HNSCC, so we briefly discussed the research progress and aimed to explore and identify the possible molecular markers and therapeutic targets.…”
Section: Head and Neck Cancers And Non-coding Rnasmentioning
confidence: 99%